TRANSGREDINDO A MATERNIDADE: DISCURSOS MÉDICOS E JURÍDICOS SOBRE ABORTO E INFANTICÍDIO EM FINS DO XIX E SÉCULO XX - SCHACTAI, DHYANDRA MONTANI (2021)
This dissertation sought to analyze the discourses present in medical theses of the Medical Schools of Salvador, Rio de Janeiro and Porto – Portugal- and how they articulate criminal proceedings and investigations into the crimes of abortion and infanticide in the Districts of Mallet and Irati – PR, and that are under the custody of the Irati Documentation and Memory Center (CEDOC/I). Aiming to establish how these discourses are produced and incorporated into everyday practices and are representations of power, knowledge and gender relations. For this purpose, we list our sources through the perspective of gender relations, defining the concepts of femininity and maternal love as discursive practices who are responsible for the articulation of the binomial "mother woman" as an innate characteristic to all women’s. Thus, by establishing the guide axis of the research, we establish the crimes of abortion and infanticide as being more than just crimes, but rather crimes against motherhood, and going against this mold present in social codes. Therefore, medical science combined with juridical discourse established social constructions about the role of women and their fertility as inherent to human reproduction, a practice that was incorporated into daily life and reproduced as a form of control and power over the female body and sexuality.